STRUKTUR KOMUNITAS PLANKTON DI PERAIRAN EKOSISTEM MANGROVE DESA MENGKAPAN KABUPATEN SIAK SEBAGAI RANCANGAN MEDIA POSTER PADA PEMBELAJARAN BIOLOGI SMA KELAS X - Afrianti, Delvi; Fauziah, Yuslim; Suwondo, Suwondo (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: The research was conducted to find out about the structure of the Plankton community in the Mangrove Ecosystem Waters of Meng Kapan Village, Siak Regency. This research was carried out for 2 months starting in July – August 2020. This study used two designs, namely exploratory research and poster design. Parameters measured are biological parameters and physical chemical parameters of the waters. The research was conducted at 3 stations. The determination of stations is done by purposive sampling technique. The results of this study indicate that the composition of the type of phytoplankton in the Mangrove Ecosystem Waters, Meng Kapan Village, Siak Regency, Riau Province. as many as 16 species and 140 individuals, the composition of zooplankton in the mangrove ecosystem waters of Meng Kapan Village found 2 classes, 4 species and 13 individuals. The data from the results of this study also has the potential to be used as a poster design for Protista material in high school Biology learning for class X.Key Words: Phytoplankton, Zooplankton, Media Poster